Pattern of variation of seedling characters in Pongamia pinnata L. (Karanja) - Ali, M.S.; Choudhary, S.C.; Alam, I.; Kumar, D.; Chakraborty, A.K.; Kumar, R. (Indian Journal of Agroforestry, 2020)
Variability pattem in five provenances of Pongamia pinnata was studied and significant differences among the provenances were recorded for all the characters. Plant height, length of branch and number of leaves showed wide range of variation. Wide difference between PCV and GCV was obtained for collar diameter, number of branch per plant and number of leaves per plant. High heritability along with moderate genetic advance was recorded for plant height indicating presence of additive gene effect; and individual plant selection for this character will be effective. High heritability with low genetic advance was recorded for length of branch and number of leaves per plant indicating presence of non-additive gene effects and therefore, these characters can be improved through hybridization programme.